Analisis Sistem Antrian Pada Brilink Elvi Juliani di Jalan Sirandorung Rantauprapat Dengan Model Antrian Single Chanel-Single Phase Pola M/M/1 - Choirunnisa, Mutiara; Harahap, Rizky Pratama; Pulungan, Riezka Amalia; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
The queuing system at BRILink Elvi Juliani on Jalan Sirandorung, Rantauprapat, uses the M/M/1 queuing model to optimize banking services. Data were obtained from observations during one operational day, involving analysis of customer arrivals and service times. The results showed that the average number of customers in the system (LS) was 0.065 customers, while the average number of customers in the queue (Lq) was 0.0004 customers, indicating a very minimal queue. The average customer waiting time in the system (Ws) was recorded at 3 minutes, with an average waiting time in the queue (Wq) of 1.8 minutes. The service busyness level (ρ) was 6.13%, indicating that the service capacity was still sufficient. With high service efficiency, this study provides insight into improving the quality of BRILink services, especially in handling higher customer volumes in the future.